Tumor-Targeting Anti-CD20 Antibodies Mediate In Vitro Expansion of Memory Natural Killer Cells: Impact of CD16 Affinity Ligation Conditions and In Vivo Priming - Capuano, Cristina; Battella, Simone; Pighi, Chiara; Franchitti, Lavinia; Turriziani, Ombretta; Morrone, Stefania; Santoni, Angela; Galandrini, Ricciarda; Palmieri, Gabriella (Frontiers in Immunology, 2018)
Natural Killer (NK) cells represent a pivotal player of innate anti-tumor immune responses. The impact of environmental factors in shaping the representativity of different NK cell subsets is increasingly appreciated. Human Cytomegalovirus (HCMV) infection profoundly affects NK cell compartment, as documented by the presence of a CD94/NKG2C+Fc∝RI≥- long-lived “memory” NK cell subset, endowed with enhanced CD16-dependent functional capabilities, in a fraction of HCMV seropositive subjects. However, the requirements for memory NK cell pool establishment/maintenance and activation have not been fully characterised yet. Here we describe the capability of anti-CD20 tumor-targeting therapeutic monoclonal antibodies (mAbs) to drive the selective in vitro expansion of memory NK cells, and we show the impact of donor' HCMV serostatus and CD16 affinity ligation conditions on this event. In vitro expanded memory NK cells maintain the phenotypic and functional signature of their freshly isolated counterpart; furthermore, our data demonstrate that CD16 affinity ligation conditions differently affect memory NK cell proliferation and functional activation, as rituximab-mediated low-affinity ligation represents a superior proliferative stimulus, while high-affinity aggregation mediated by glycoengineered obinutuzumab results in improved multifunctional responses. Our work also expands the molecular and functional characterization of memory NK cells, and investigates the possible impact of CD16 functional allelic variants on their in vivo and in vitro expansion. These results reveal new insights in Ab-driven memory NK cell responses in a therapeutic setting, and may ultimately inspire new NK cell-based intervention strategies against cancer, in which the enhanced responsiveness to mAb-bound target could significantly impact therapeutic efficacy.